Revolutionary War on Wednesday - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2000)
Using their magic tree house, Jack and Annie travel back to the time of the American Revolution and help General George Washington during his famous crossing of the Delaware River.
Wednesday! -- Day or Night? -- It's Time -- Commander-in-Chief -- The Letter -- Crossing the Delaware -- Spies! -- These Are the Times -- Flash! -- This Peaceful Place.
"A Stepping stone book."
07-10.
2-5.
Keywords: Washington, George, -- 1732-1799 -- Juvenile fiction; Washington, George, -- 1732-1799; Time travel -- Juvenile fiction; Magic -- Juvenile fiction; Happiness -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Space and time -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Fantasy -- Juvenile fiction; Tree houses -- Juvenile fiction; Magic -- Fiction; Time travel -- Fiction; Magic -- Fiction; Adventure stories; Brothers and sisters; Fantasy; Happiness; Magic; Space and time; Time travel; Tree houses; Voyages and travels; United States -- History -- Revolution, 1775-1783 -- Juvenile fiction; United States; Action and adventure fiction; Fiction; History; Juvenile works